Ujala class 1 feroz sons urdu series - Shazia, Islam (Feroz sons Lahore, 2004)
"Ujala" is a popular textbook series used in many Pakistani schools for primary classes. The series is known for its engaging content, colorful illustrations, and focus on developing basic reading, writing, and arithmetic skills.